Occupational Psychosocial Risk Factors in Academics of Higher Education Institutions in Latin America: a Systematic Review - Monroy-Castillo, Alisma (2019)
The purpose of this systematic review was to characterize job psychosocial risk factors and their consequences on subjective indicators and health objectives in university professors from Spanish-speaking countries in Latin America.  The web search included PubMed, EBSCO, PsycINFO, PSICODOC, LILACS, MEDIGRAPHIC, IMBIOMED, Redalyc, Dialnet, Scielo and Doyma. Three reviewers selected the articles for review independently and assessed their methodological quality according to the STROBE guideline. As a result, 8 articles met the inclusion and exclusion criteria. The results confirmed the presence of different psychosocial risk factors derived from working conditions linked to the higher education international policies. In the study, the relationships of these factors with different psychological and biological health effects are shown. The need for more and better quality studies and the importance of implementing health and welfare prevention programmes in the academic sector are also discussed.